1994
DOI: 10.1021/bi00178a025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Bacteriorhodopsin and Artificial Pigments

Abstract: The structure of bacteriorhodopsin based on electron microscopy (EM) studies, as provided in Henderson et al. (1990), is refined using molecular dynamics simulations. The work is based on a previously refined and simulated structure which had added the interhelical loops to the EM model of bR. The present study applies an all-atom description to this structure and constraints to the original Henderson model, albeit with helix D shifted. Sixteen waters are then added to the protein, six in the retinal Schiff ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
117
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(134 citation statements)
references
References 74 publications
(123 reference statements)
16
117
1
Order By: Relevance
“…23 All the simulation results were represented using Visual Molecular Dynamics (VMD) soware, version 1.9. 24 …”
Section: Model and Methodsmentioning
confidence: 99%
“…23 All the simulation results were represented using Visual Molecular Dynamics (VMD) soware, version 1.9. 24 …”
Section: Model and Methodsmentioning
confidence: 99%
“…There is experimental evidence for internal bound water in bR (34)(35)(36)(37). Molecular dynamics calculations on the bR structural model proposed by Henderson et at (13) orient a chain of water molecules just between D96 and the Schiff base as presented in the scheme (38,39).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the refined structure of bacteriorhodopsin reported in [31] was used as a starting point for all the computations. This structure, corresponding to the bR 568 pigment, is depicted in Figures 2a and 5b.…”
Section: Quantum Chemistry Of In Situ Retinalmentioning
confidence: 99%
“…It has been observed that modification of protein groups in the vicinity of the retinal Schiff base shifts considerably the bR absorption spectrum [69] and affects drastically the rates of both thermally- [70] and photo- [71,72] [75,76,77]. At present, there exist a number of ab initio as well as semi-empirical techniques which try to account for the realistic atomic structure and charge distribution of the environment via explicit incorporation of protein (or solution) point charges in the electronic Hamiltonian of the quantum chemically treated substrate [78,79,80,81,82,83].In our study, the refined structure of bacteriorhodopsin reported in [31] was used as a starting point for all the computations. This structure, corresponding to the bR 568 pigment, is depicted in Figures 2a and 5b.…”
mentioning
confidence: 99%
See 1 more Smart Citation